Original paperEFFECT OF LOW-IMPACT AEROBIC DANCE EXERCISE ON PSYCHOLOGICAL HEALTH (STRESS) AMONG SEDENTARY WOMEN IN MALAYSIA - Mastura, J.; Omar Fauzee, M.S.; Bahaman, A.S.; Rashid, S. Abd.; Somchit, M.N. (Biology of Sport, 2012)
The present study investigated the effect of twelve weeks of low-impact aerobic dance exercise intervention (“aero-mass” dance exercise) on psychological health (stress) among sedentary working women, specifically in Malaysia. Sedentary participants (age range = 40 – 55 years; N = 40: BMI > 25) were randomly assigned to two groups: an intervention treatment of “aero mass aerobic dancing” and conventional low-impact aerobic dancing. Classes were held for 50 minutes, 3 days per week, for 12 weeks. Repeated measures were examined at week 1, week 8 and week 12. Mixed repeated ANOVA revealed statistically significant time effects for Total Stress Scores (p < 0.01) with eta square =0.59 (large effect) at week 8 and week 12. Furthermore, the time by group interaction was also statistically significant for total stress score (p < 0.05) with eta square = 0.18 (large effect). In addition, the result for between-subject effects indicates significant F (1, 38)=7.74, p < 0.05, eta = 0.17, and therefore there was a significant difference in the stress level scores in the intervention group compared to the control group. Subjects of the intervention group, “aero mass aerobics dancing”, experienced the most benefits.